2021
DOI: 10.1016/j.vhri.2020.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness of Lenvatinib in the Treatment of Patients With Unresectable Hepatocellular Carcinomas in Japan: An Analysis Using Data From Japanese Patients in the REFLECT Trial

Abstract: Background: Hepatocellular carcinoma (HCC) is one of the leading causes of cancer-related mortality in Japan. Prognosis is poor, and until recently sorafenib was the only treatment option available for patients with unresectable disease. Lenvatinib is the first therapy to demonstrate noninferiority to sorafenib. An analysis was conducted using clinical data from Japanese patients in the phase III REFLECT trial to assess the cost-effectiveness of lenvatinib versus sorafenib for first-line treatment of unresecta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Cai et al (31) confirmed that lenvatinib was economical compared to sorafenib when considered donations. Relevant literature outside of China (29,(32)(33)(34) showed that ICERs of lenvatinib and T + A compared with sorafenib were significantly higher than the threshold in China, which indicated that lenvatinib and T + A were not more cost-effective than sorafenib in China.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cai et al (31) confirmed that lenvatinib was economical compared to sorafenib when considered donations. Relevant literature outside of China (29,(32)(33)(34) showed that ICERs of lenvatinib and T + A compared with sorafenib were significantly higher than the threshold in China, which indicated that lenvatinib and T + A were not more cost-effective than sorafenib in China.…”
Section: Discussionmentioning
confidence: 99%
“…With no direct randomized controlled trials between groups of drugs, indirect comparisons are necessary. Most previous studies (18,29,(32)(33)(34)(35)(36)(37)(38) have used a common control drug as a bridge and adopted the constant HR assumption. This method requires that the KM curves of the test group and control group obey the assumption of equal proportions.…”
Section: Discussionmentioning
confidence: 99%
“…There have been several published economic evaluations of lenvatinib in different settings; however, they mainly compared lenvatinib with sorafenib. These analyses showed that across the world, including Japan [22,23], Australia [19], Canada [18,24], and China [25], lenvatinib is more cost-effective than sorafenib for HCC patients. Wen et al [26] and Su et al [27] focused on the cost-effectiveness of an ICI plus a VEGF inhibitor vs. a tyrosine kinase inhibitor (atezolizumab plus bevacizumab vs. sorafenib) for the treatment of advanced HCC in China.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the ICI+Lenva and ICI+Others groups had similar follow-up periods and comparable baseline characteristics, and no significant differences were observed between these two groups in the short-term and long-term efficacy endpoints. In addition, lenvatinib performed well in a cost-effectiveness analysis (25)(26)(27)(28)(29), so the rechallenge of lenvatinib plus ICI is likely to be a better choice. Future prospective clinical trials are needed to prove the above hypothesis.…”
Section: Discussionmentioning
confidence: 99%